El bovarysmo (2011)
ABSTRACT: After a short pass through a brief love story, Gustave Flaubert work that constituted a new love and femininity paradigm found a revolutionary place. Jules de Gaultier formulations where the Bovarysme term was introduced in psychiatry are restudy to show this notion destiny in the Lacanian psychoanalysis.